Réflexions sur les variations, dans le temps et dans l'espace, des ressources alimentaires de deux espèces sympatriques de semnopithèques - Claude Marcel Hladik; Annette Hladik (Revue de Primatologie)
Our field work, the basis of this paper, was conducted in Ceylon (Sri Lanka) in 1969 and 1970. It focused on food choices and space use by two sympatric species of leaf monkey, Presbytis senex and Presbytis entellus. Although the diets of these two leaf-monkeys were originally considered quite similar, quantifying food intake revealed differences that persisted through the year. The plants P. senex ate were the area’s most common tree species, which had leaves with the greatest fiber content. A low-altitude aerial photograph was clear enough to identify and measure all food-producing trees, and one could outline the territories of the different groups studied from observations a year earlier by a Smithsonian team. We calculated the food resources available to each territorial group of primates. Groups of P. senex were smaller, and moved shorter distances within smaller territories of 2-7 ha. P. entellus lived in larger groups, moved longer distances in larger territories of 10-15 ha, and fed from more different plant species with higher average food quality The trade-off between living on lower-quality, more abundant foods, entailing diminished movement over small territories, and living on a higher diversity of higher quality foods that require moving further and defending larger territories, was discussed in terms of taste perception, based either on satiety or on immediate sensory reward. More generally, there is a continuum between species with a lower diversity of foods, generally of lower quality, occupying smaller territories, and species with more diverse diets of higher average quality, that require moving longer distances and defending bigger territories.